PHYSIOCHEMICAL CHARACTERIZATION OF THE GREEN COCONUT PULP SUBMITTED TO THE SLOW AND FAST FREEZING - Soares, Gustavo Lana [UNESP]; Daiuto, Erica Regina [UNESP]; Mendonca, Veridiana Zocoler de [UNESP]; Vietes, Rogerio Lopes [UNESP] (Univ Federal Mato Grosso, 2015)
The green coconut pulp is a discard of the coconut water industry, performing besides environmental concern a great waste. The aim of work was to characterize the green coconut pulp of the Ana variety, by their physiochemical and biochemistries characteristics. After coconut water extraction, were obtained pulp samples with 2 cm of diameter and 0.5 cm of thickness. The samples were conditioned in transparent polypropylene packing, under vacuum, and submitted to the slow (CL) and fast (CR) freezing. The samples stayed in domestic freezer (-20 degrees C) and were evaluated to the 0, 30, 60 and 9 storage days. The in natura pulp was characterized as the centesimal composition (protein, lipids, fiber, ash and moisture). In the samples submitted to the slow and fast freezing was determined the coloration, firmness, hidrogenionic potential (pH), titratable acidity (AT), soluble solids (SS), phenolics content and antioxidant activity (by DPPH). The in natura pulp revealed considerable fibers content (10.5%) and lipids (10.1%). The frozen pulp presented stability as the parameters evaluated during the storage period. The fast freezing resulted in superior quality of the evaluated samples.
Keywords: Cocos nucifera L.; dwarf variety; waste utilization; conservation